PKM IMPLEMENTATION OF 5R IN SDIT CITRA AZ-ZAHRA - Ratih Ikha Purnama Sari; Rini Setiowati; Nur Arifiya (Universitas PGRI Sumatera Barat, 2022)
This PKM aims to: (1) determine the application of 5R (Clean, Concise, Neat, Careful, Diligent), (2) determine the effect of 5R implementation on the readiness of school children to receive lessons from teachers in SDIT Citra Az-Zahra's class. This PKM is carried out on an ex post facto basis. The population in the implementation of this community service is in Class V SDIT Citra Az-Zahra, totaling 30 students. Based on the results of the PKM, it is hoped that a positive relationship can be obtained on the implementation of 5R at SDIT Citra Az-Zahra.